Ekosistem Digital Sebagai Wadah Peningkatan Kapasitas Mitra PT Hanjaya Mandala Sampoerna Di Kota Palu - Dimas Dimas; Niluh Putu Evvy Rossanty; Harnida Wahyuni Adda (Manajemen Kreatif Jurnal, 2023)
The digital ecosystem is a source of information technology that is interrelated and can be used as a unified whole. So, this system is likely to be used by various parties such as consumers, suppliers, data providers. Trading partners, and many more. This digital ecosystem formed by PT Hanjaya Mandala Sampoerna connects distributors, retail aggregators and companies as facilitators. The application used to run this digital ecosystem is named AYO MITRA SRC, then with this application, distributors or so-called Partners will provide ordering services through the Ayo SRC application, this provides convenience and increases effectiveness in transactions, which does not need to exist queuing to select and count goods resulting in an increase in service quality and partner capacity, one of which is in terms of neater and more structured sales records.